FAKTOR-FAKTOR YANG MEMPENGARUHI PROSES PENGAMBILAN KEPUTUSAN TENTANG PASANGAN HIDUP (STUDY KASUS WANITA KARIR DI KECAMATAN TAMPAN KOTA PEKANBARU) - Yanti, Krisna Damai; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study was conducted on unmarried women at Kecamatan Tampan Kota Pekanbaru. The purpose of this study is to determine the criteria of career women in determining the spouse at Kecamatan Tampan Kota Pekanbaru. The focus of this research is the process of considering a spouse for a career woman at Kecamatan Tampan Kota Pekanbaru. Sampling technique in this research is accidental sampling. and set the sample size of 97 people. The author uses quantitative methods and Instruments data is observation, questionnaires and documentation. The research found the respondent's criteria in choosing the spouse at Kecamatan Tampan Kota Pekanbaru. were as follows: Education, stakeholder findings showed that respondents were more interested in men with educational background S2 (35.1%) and S3 (40.2%). The majority of career women studied were more likely to choose men with S1-S3 education as a spouse. Occupation, Generally respondents prefer men who contribute greatly in plantation sector (28.9%), followed by men who work as educators (21.6%), the rest of the respondents prefer spouses who work as employees , traders, and civil servants. Income, Responsible stakeholder's outcome on income classification dominated by spouse who have income more than Rp 2,500,000 with percentage of choice as much 91,7%, whereas percentage of respondent response about spouse income criteria <2,500.000 is as much 82,4 %. Keywords: Career Women, Factor, Gender